Multiple door security system - Abu Hanieh, Saif; Haydar, Samir (My University, 2018)
We plane to design a security system to open multiple doors for authorized persons. These authorized persons will control the opening and closing of the doors using GSM and voice recognition technologies. When any person makes a call with SIM card through GSM technology, the micro controller will check if its number is authorized or not, if it authorized the LCD will print (speak now) and the Arduino1 will send a pulse for Arduino2 to operate the speech module, if you speak (right) the right door will open. and if speak (left) ,the left door will open. If its unauthorized number, the LCD will not print (speak now) and Arduino1 will not send a pulse for arduino2 and the speech module will remain unoperated .